Nitrogen budgets for freshwater aquaculture and mariculture in a large tropical island – A case study for Hainan Island 1998–2018. (May 2022) - Jiao, Yangmei; Zhao, Hongwei; Li, Zichen; Tang, Xianming; Li, Yuanchao; Chen, Shiquan; Zhu, Zhiqiang; Wang, Tao; Strokal, Maryna; Kroeze, Carolien
Abstract: Nitrogen is an essential nutrient in aquaculture. It is also an important factor in coastal and river eutrophication. We present an island-scale model to study the nitrogen flows in different aquaculture systems in Hainan Island during 1998–2018. The result indicated that nitrogen losses associated with pond sludge, wastewater discharge and gaseous emission increased by a factor of 1.4, 4.6 and 3.2, respectively. Sludge and wastewater account for 84% of the total losses to the environment. During the past 20 years, aquacultural yields and the nitrogen use efficiency (NUE) improved considerably in Hainan Island. Nevertheless, nitrogen losses to the environment increased significantly as well, with negative effects for local ecosystems. In the future, sustainable aquacultural practices are needed to improve NUE and to reduce nitrogen losses to the environment. Highlights: Nitrogen flows in different aquaculture systems in Hainan Island during 1998–2018. Nitrogen losses from aquaculture ponds to the environment increased significantly. Aquaculture had negative effects for local ecosystems.